The Hybridization of Punishment and Welfare: The legal treatment of insane offenders in Switzerland 1890–1970 - Germann, Urs (GLOSSAE. European Journal of Legal History, 2023)
This chapter deals with the treatment of insane offenders in Switzerland between the late 19th century and the 1960s, and how it became part of the legal policy agenda. The implementation of the Swiss criminal code after it came into force in 1942 is also examined. From the onset, Swiss psychiatrists were important players in drafting the first Swiss criminal code. Together with other progressives, they developed a set of measures based on earlier forms of administrative detention, while simultaneously advocating important demands of legal positivism aimed at protecting society. This hybrid broke through the traditional demarcation between repression and prevention, at legal, institutional and individual levels. The new Swiss criminal code of 1942, similarly, was a hybrid between repression and welfare provisions in its security and treatment measures. Psychiatry thereby became part of the correctional system, while the majority of mentally ill offenders ended up, de facto, in penal institutions. This led offenders to often be stigmatised as abnormal in criminal proceedings; they were imprisoned for indeterminate periods of time and had little or limited access to psychiatric care. Criminal law thereby became more open to prevention and protection considerations, and hence to public welfare concerns. In retrospect, however, the development is part of an unfinished and inherently ambivalent modernisation process, and an example of the “muddling through” typical of how marginalized groups are dealt with in federalist Switzerland.